(untitled) (Journal of Human Sciences, 2021)
This study aimed to identify the obstacles to developing critical thinking (the skill of thinking itself) among students of basic education from the point of view of their teachers in the city of Marj, as well as to identify (administrative obstacles) and also (obstacles related to the student) among students of basic education from the point of view of their teachers in the city of Al-Marj And the identification of the most influential obstacles on the development of critical thinking among students of basic education from the point of view of their teachers in the city of Marj Administrative - obstacles related to the classroom environment - obstacles specific to the student - obstacles specific to the teacher)And a questionnaire was applied to a sample of basic education amounting to(82) female teachers, after starting from its validity and stability, it is composed of 55 paragraphs consisting of five(critical thinking skill –administrative obstacles – obstacles related to the classroom environment - special obstacles for the student-special obstacles by the same teacher) and the descriptive method was used as it is appropriate and appropriate the current research The results showed that the obstacles to developing critical thinking (the skill of thinking itself) were high at the level (0.01), as well as (administrative obstacles), (obstacles related to the student) and (obstacles related to By the teacher) and (obstacles related to the classroom environment) were high at the level (0.01)